Gambaran Perilaku Manajemen Perawatan Penderita DM - Mu'in, Muhammad; Nursasi, Astuti Yuni; Wiarsih, Wiwin (Jurusan Keperawatan FIKES UNSOED, 2014)
The aim of research were to explore experiences of Diabetes patient performing care at home. This research used qualitative descriptive phenomenology method and data collected by in-depth interview. Participants were Diabetes patient collected by criterion sampling technique. Data gathered were in form of record of in-depth interview and field note transcribed and analyzed by Collaizi’s method. Result of research identified 10 themes, consist of alteration caused by diabetes and its complication, responds to diagnosis and care management, dietetic management, physical exercise management, medical treatment management, health center visits management, use of alternatives medicine, spiritual effort in managing DM, motivation to perform care, spiritual experience and life lesson.